2019
DOI: 10.1101/767947
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Increase in egg resistance to desiccation in springtails correlates with blastodermal cuticle formation: eco-evolutionary implications for insect terrestrialization

Abstract: Land colonization was a major event in the history of life. Among animals, insects had a staggering terrestrialization success, due to traits usually associated with post-embryonic life stages, while the egg stage has been largely overlooked in comparative studies. In many insects, after blastoderm differentiation, the extraembryonic serosal tissue wraps the embryo and synthesizes the serosal cuticle, an extracellular matrix that lies beneath the eggshell and protects the egg against water loss. In contrast, i… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 60 publications
(72 reference statements)
0
3
0
Order By: Relevance
“…In arthropods and amniotes, it has been suggested that the presence of specialized extra-embryonic tissues is correlated with terrestrialization and egg deposition in corresponding habitats [3,13,74,75]. Extra-embryonic tissues surrounding the developing embryo might serve as a protective barrier against mechanical stress and desiccation and, thus, allowed arthropods and amniotes to conquer new habitats [3,13,74,75].…”
Section: Reproductive Strategies and Associated Modifications Of Dors...mentioning
confidence: 99%
See 1 more Smart Citation
“…In arthropods and amniotes, it has been suggested that the presence of specialized extra-embryonic tissues is correlated with terrestrialization and egg deposition in corresponding habitats [3,13,74,75]. Extra-embryonic tissues surrounding the developing embryo might serve as a protective barrier against mechanical stress and desiccation and, thus, allowed arthropods and amniotes to conquer new habitats [3,13,74,75].…”
Section: Reproductive Strategies and Associated Modifications Of Dors...mentioning
confidence: 99%
“…In arthropods and amniotes, it has been suggested that the presence of specialized extra-embryonic tissues is correlated with terrestrialization and egg deposition in corresponding habitats [3,13,74,75]. Extra-embryonic tissues surrounding the developing embryo might serve as a protective barrier against mechanical stress and desiccation and, thus, allowed arthropods and amniotes to conquer new habitats [3,13,74,75]. On the other hand, while onychophorans are exclusively terrestrial, they are all confined to humid microhabitats irrespective of their developmental mode or specific distribution (figure 2 A,B ; [9,38,39]).…”
Section: Reproductive Strategies and Associated Modifications Of Dors...mentioning
confidence: 99%
“…That both crickets and chickens, and mosquitoes and mice, develop within a fluid-filled amniotic cavity represents a convergent solution to common challenges, including the demands of a fully terrestrial lifestyle. Adaptations of the egg to prevent desiccation, chiefly including the EE tissues, have enabled insects and amniotes to colonize diverse ecological niches away from the aquatic and humid habitats to which species such as amphibians and springtails are constrained [7,8].…”
Section: Extraembryonic Tissues As a Common Strategy To The Challenge...mentioning
confidence: 99%